Evaluation of hardness and wear resistance of nano-sized titanium-carbide-reinforced commercially cast aluminum alloy matrices - Mohammad Mafi; Behrooz Ghasemi; Omid Mirzaee (Mechanics of Advanced Composite Structures)
Production of aluminum matrix composites is widespread because these material provide enhanced mechanical properties compared to aluminum. One the most important parameters of metal matrix composite production is uniform distribution of reinforcing nanoparticles in matrices using the stir-casting method. Second is ensuring high wettability, which is determined by evaluating the properties of materials on a nano-scale. In this study, aluminum composites were reinforced with titanium carbide nanoparticles coated with aluminum to increase wettability. Particles were prepared and added to a molten aluminum alloy. After stirring the particle mixture as a variable parameter, casting was conducted in a sand mold. To evaluate the mechanical properties of the composite, the Brinell test was used to determine hardness and the pin-on-disk test was used to measure wear rate and the friction coefficient. The results showed that the hardness of the composite increased from 84 BHN to 134 BHN as nanoparticles were added to the alloy. Additionally, as stirring time increased, weight loss decreased with respect to the base alloy, while the coefficient of friction increased.